2022
DOI: 10.21608/eajbsa.2022.276328
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Disinfestation of Stored Grain Insects Using Solar Energy

Abstract: Chemical control, especially fumigants, is the most used method to control stored-grain pests. A safer alternative for disinfestation is to heat grains to a temperature of 50-60 o C. However, this alternative consumes high thermal energy due to the relatively high temperature required to achieve the required goal. In the present paper, a grain solar heating system has been developed to achieve this high temperature/short time technique to control Callosobruchus maculatus, one of the most common pests of many l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Stored in eggs, larvae and pupae, detailed results in Egypt showed that the spoilage was 67.60%, while the kill was 4.30% in the bags. The best weight and quantity of black grains inside the bags gave excellent results, which was 16 kilograms of rice [10]. The technology of recording sunlight against warehouse insects is not new.…”
Section: Introductionmentioning
confidence: 99%
“…Stored in eggs, larvae and pupae, detailed results in Egypt showed that the spoilage was 67.60%, while the kill was 4.30% in the bags. The best weight and quantity of black grains inside the bags gave excellent results, which was 16 kilograms of rice [10]. The technology of recording sunlight against warehouse insects is not new.…”
Section: Introductionmentioning
confidence: 99%